Prevention of perioperative venous thromboembolism in pediatric patients: Guidelines from the Association of Paediatric Anaesthetists of Great Britain and Ireland (APAGBI). Issue 5 (27th April 2018) - Morgan, Judith; Checketts, Matthew; Arana, Amaia; Chalmers, Elizabeth; Maclean, Jamie; Powis, Mark; Morton, Neil; ,
Summary: The Association of Paediatric Anaesthetists of Great Britain and Ireland (APAGBI) Guidelines Working Group on Thromboprophylaxis in Children has reviewed the literature and where possible provided advice on the care of children in the perioperative period. Areas reviewed include the incidence of perioperative venous thromboembolism (VTE), risk factors, evidence for mechanical and chemical prophylaxis, and complications. Safe practice of regional anesthesia with anticoagulant prophylaxis is detailed. In summary, there are few areas of strong evidence. Routine prophylaxis cannot be recommended for young children. Postpubertal adolescents (approximately 13 years and over) are at a slightly increased risk of VTE and should be assessed for prophylaxis and may warrant intervention if other risk factors are present. However, the incidence of VTE is significantly lower than in the adult population. This special interest review presents a summary and discussion of the key recommendations, a decision‐making algorithm and a risk assessment chart. For the full guideline, go towww.apagbi.org.uk/publications/apa-guidelines .